IL-6/STAT3/Foxo1 axis as a target of lycopene ameliorates the atrazine-induced thymic mitophagy and pyroptosis cross-talk. Issue 17 (3rd August 2022) - Zhu, Shi-Yong; Li, Chen-Xi; Tong, Yu-Xuan; Xu, Ya-Ru; Wang, Zhao-Yi; Li, Jin-Long
Abstract : The thymus is central architecture for lymphoid cells. Atrazine exposure induces thymic mitophagy and pyroptosis cross-talk. Lycopene has the potential role in prevention the atrazine's toxic effect by targeting the IL-6/STAT3/Foxo1 axis. Abstract : The intensive adoption of atrazine (ATZ) is a source of a persistently widespread pollutant in daily life. However, ATZ is still used as an essential herbicide in numerous countries because its toxic effect is not addressed as a public health concern. This study found that ATZ exposure caused mitophagy and pyroptosis crosstalk in the thymus. And it could destroy the thymus architecture, inducing immunodeficiency. Lycopene (LYC), a natural bioactive component, is applied to reduce the risk of chronic diseases caused by environmental factors. This work also investigated the health benefits of LYC in the ATZ-induced toxic effect on the thymus. LYC could ameliorate the ATZ-induced mitophagy and pyroptosis. LYC modulated the IL-6/STAT3/Foxo1 axis, improving the level of CD45 in the thymus. This work sheds light on the toxic effect of ATZ on the thymus, and it will provide evidence for ATZ health risks. Additionally, the finding also underscores a novel target of LYC in maintaining thymic homeostasis in ATZ exposure.